2014
DOI: 10.1136/oemed-2014-102161
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative occupational shoulder exposures and surgery for subacromial impingement syndrome: a nationwide Danish cohort study

Abstract: ObjectivesThe primary aim was to examine exposureresponse relationships between cumulative occupational shoulder exposures and surgery for subacromial impingement syndrome (SIS), and to compare sexspecific exposure-response relationships. The secondary aim was to examine the time window of relevant exposures. Methods We conducted a nationwide register study of all persons born in Denmark (1933Denmark ( -1977, who had at least 5 years of full-time employment. In the follow-up period (2003)(2004)(2005)(2006)(200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
130
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(139 citation statements)
references
References 43 publications
7
130
2
Order By: Relevance
“…(Schall Jr et al 2014 While estimates of muscular effort observed in this study were relatively low, the repetitive nature of ophthalmologic examinations and their cumulative effects over time may still contribute to the high prevalence of musculoskeletal pain among ophthalmologists. Several prospective studies have suggested that cumulative exposure to sustained, forceful muscular exertions may contribute to neck and shoulder pain among workers in various occupations (Dalbøge et al 2014;Hanvold et al 2013). Furthermore, duration of computer and mouse use, the clinical task observed to be most frequently performed among ophthalmologists in the current study, has been causally linked to musculoskeletal symptoms of the neck and arm (Blatter and Bongers, 2002;Jensen et al 2002;Marcus et al 2002;Waersted et al 2010).…”
Section: Discussionmentioning
confidence: 80%
“…(Schall Jr et al 2014 While estimates of muscular effort observed in this study were relatively low, the repetitive nature of ophthalmologic examinations and their cumulative effects over time may still contribute to the high prevalence of musculoskeletal pain among ophthalmologists. Several prospective studies have suggested that cumulative exposure to sustained, forceful muscular exertions may contribute to neck and shoulder pain among workers in various occupations (Dalbøge et al 2014;Hanvold et al 2013). Furthermore, duration of computer and mouse use, the clinical task observed to be most frequently performed among ophthalmologists in the current study, has been causally linked to musculoskeletal symptoms of the neck and arm (Blatter and Bongers, 2002;Jensen et al 2002;Marcus et al 2002;Waersted et al 2010).…”
Section: Discussionmentioning
confidence: 80%
“…We used data from a nationwide cohort study, which included the entire Danish working population as described previously 6. The cohort included all persons born in Denmark (excluding Greenland) between 1 January 1933 and 31 December 1977, who were alive and lived in Denmark on 31 December 2002 according to the Civil Registration System,12 and had at least 5 years of full-time employment between 1 January 1993 and 31 December 2007 according to the Supplementary Pension Fund Register 13.…”
Section: Methodsmentioning
confidence: 99%
“…Persons were excluded in case of surgery for any shoulder disorder before 31 December 2002 according to the Danish National Patient Register 12. The cohort comprised 2 374 403 persons with 14 118 first-time events of surgery for SIS during follow-up from 1 January 2003 to 31 December 2008 6. Follow-up time was calculated from 1 January 2003 or the year after they reached 5 years of full-time employment, whichever came later, until surgery for SIS or censoring due to surgery for any other shoulder disorder, death, disappearance, emigration (including change of address to Greenland) or 31 December 2008, whichever came first 6.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of the upper trapezius, mean muscle activation levels were also reduced during use of the upright system. Although cumulative exposure to sustained and/or forceful muscular exertions is associated with musculoskeletal health outcomes (Hanvold et al, 2013;Dalboge et al, 2014), the magnitude of risk reduction associated with a given reduction in muscle activation is not well characterized. Therefore, while the observed reductions in biomechanical loading are mostly positive, definitive conclusions about the potential of the upright system to prevent musculoskeletal health outcomes are premature.…”
Section: Discussionmentioning
confidence: 99%